2019
DOI: 10.3390/cancers12010084
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data on Cabozantinib in Previously Treated Patients with Metastatic Renal Cell Carcinoma: Focus on Sequences and Prognostic Factors

Abstract: Cabozantinib is approved for the treatment of renal cell carcinoma (RCC). However, prognostic factors are still lacking in this context. The aim of this study was to evaluate prognostic factors in RCC patients treated with second- or third-line cabozantinib. A multicenter retrospective real-world study was conducted, involving 32 worldwide centers. A total of 237 patients with histologically confirmed clear-cell and non-clear-cell RCC who received cabozantinib as second- or third-line therapy for metastatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…VHL gene malfunction is detected in the overwhelming majority of the cases, resulting in a pseudo-hypoxic status that promotes angiogenesis [ 5 ]. The implementation of antiangiogenic therapies with tyrosine kinase inhibitors has improved the prognosis of many of these patients [ 6 , 7 ]. However, its efficacy is limited due to the development of resistant-to-therapy cell clones [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…VHL gene malfunction is detected in the overwhelming majority of the cases, resulting in a pseudo-hypoxic status that promotes angiogenesis [ 5 ]. The implementation of antiangiogenic therapies with tyrosine kinase inhibitors has improved the prognosis of many of these patients [ 6 , 7 ]. However, its efficacy is limited due to the development of resistant-to-therapy cell clones [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cabozantinib is approved for the treatment of patients with metastatic RCC in treatment-naïve adults with intermediate or poor-risk features and for adults that have progressed to prior vascular endothelial growth factor/receptor inhibitors. In 2019, we reported the results of an international retrospective real-world analysis on cabozantinib in previously treated patients with metastatic RCC, which was aimed at investigating the presence of prognostic factors in this context [ 10 ]. We observed that both hemoglobin (Hb) levels and International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) prognostic models were associated with the outcome of patients receiving cabozantinib [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, we reported the results of an international retrospective real-world analysis on cabozantinib in previously treated patients with metastatic RCC, which was aimed at investigating the presence of prognostic factors in this context [ 10 ]. We observed that both hemoglobin (Hb) levels and International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) prognostic models were associated with the outcome of patients receiving cabozantinib [ 10 ]. Furthermore, the median time to strategy failure (TTSF) was 11.57 months with the sequence cabozantinib–nivolumab and 25.64 months with nivolumab–cabozantinib [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed activity of cabozantinib in patients who had previously received ICI, with a DCR of 64% and median OS of 15.8 months (range 10.3 -20.7 months). Similar findings were seen in the METEOR study as well as other retrospective series [16][17][18][19][20]. Importantly, we included patients treated immediately after first-line ICI-based combination therapy (Table 3), which represents a group where data is lacking on the optimal treatment strategy.…”
Section: Discussionmentioning
confidence: 86%